2018
DOI: 10.1037/law0000163
|View full text |Cite
|
Sign up to set email alerts
|

Perpetually stigmatized: False confessions prompt underlying mechanisms that motivate negative perceptions of exonerees.

Abstract: Even in the fortunate instances of being exonerated of their wrongful convictions, exonerees often struggle to assimilate back into society. Although research has established that exonerees experience stigma and a general lack of reintegration support, little is known about underlying reasons that motivate such negative perceptions. This research examined whether the evidence and crime associated with a wrongful conviction could initiate a process that alters people’s perceptions of exonerees’ intelligence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 40 publications
3
30
1
Order By: Relevance
“…Building on the idea that false confessors are stigmatized more than other exonerees (Clow & Leach, ; Scherr et al, a), our findings illustrate how stigma can impede false confessors' ability to win financial restitution for their wrongful imprisonment. Consistent with traditional theories of stigma (Jones et al, ) and prior research (Savage et al, ), mock jurors rated an exoneree who falsely confessed as more responsible for his own conviction than one who was misidentified by an eyewitness—even if he confessed under coercion.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Building on the idea that false confessors are stigmatized more than other exonerees (Clow & Leach, ; Scherr et al, a), our findings illustrate how stigma can impede false confessors' ability to win financial restitution for their wrongful imprisonment. Consistent with traditional theories of stigma (Jones et al, ) and prior research (Savage et al, ), mock jurors rated an exoneree who falsely confessed as more responsible for his own conviction than one who was misidentified by an eyewitness—even if he confessed under coercion.…”
Section: Discussionsupporting
confidence: 58%
“…As predicted, participants rated the false confessor as less competent, less warm, more likely to be guilty, and less deserving of government assistance than other exonerees. Similarly, Scherr, Normile, and Putney () found that individuals rated an exoneree who falsely confessed as less intelligent than an exoneree who was misidentified by an eyewitness, and these ratings ultimately predicted the degree to which they viewed the exoneree as deserving of reintegration services (e.g., job training).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The enduring negative stigma associated with falsely confessing also undermines people’s willingness to financially compensate these innocents (Kukucka & Evelo, 2019; Luna & Kieckhaeifer, 2018). False confessions can be so influential as to precipitate a series of negative judgments of these individuals as lacking intelligence, suffering from mental health issues, not entirely innocent, and, ultimately, less deserving of government-sponsored reintegration aids such as psychological and career counseling and job training (Scherr, Normile, & Putney, 2018). Along with replicating the undermining series of negative judgments associated with wrongful convictions based on false confessions, the same series of judgments follows after innocents offer false guilty pleas (Scherr et al, 2019).…”
Section: Stage 5: Postconviction Appeals and Exonerationmentioning
confidence: 99%
“…Third, there is mounting evidence that exonerees who falsely confessed to the crime of which they were wrongly convicted are more stigmatized than other exonerees. In various studies, laypeople rated false confessors as less warm, intelligent, and mentally healthy than other exonerees (Clow & Leach, 2015b;Scherr et al, 2018b;, blamed them more heavily for their wrongful conviction (Kukucka & Evelo, 2019;Savage et al, 2018;Scherr et al, 2020), and saw them as less deserving of financial compensation (Kukucka & Evelo, 2019) or reintegration services such as psychological counseling (Scherr et al, 2018b). As a result, false confessors may show poorer mental health than other exonerees, but no study has tested this possibility.…”
Section: Introductionmentioning
confidence: 99%